Supervisors Professionality Implementation in Improving The Creativity of Islamic Religious Education Teachers: Study of Middle School Learning Management in Sumedang Regency - Asep Ganjar Sukarelawan; Heru Sujiarto; Andriana Gaffar; Dinny Mardiana (Journal of Social Science, 2022)
This research is based on the non-optimal professionality of supervisors, which in turn has an impact (outcome) on the quality of learning output(output)in the form of increased creativity of teachers who overall the relationship between these components forms a system. The main problem of this research is how the implementation of supervision of the creativity of Islamic Education teachers in improving the quality of learning, both from planning, implementation, evaluation, follow-up. This study aims to find out the picture related to the implementation of supervision on planning, implementation, evaluation and follow-up in increasing the creativity of Teachers of Islamic Religious Education Junior High School in Sumedang Regency. This research uses a qualitative approach using descriptive analysis. Data collection techniques are carried out through observation, interviews and documentation studies. Data analysis is done through data reduction, organizing and grouping, examination, interpretation, and verification. The data analysis is further described according to the problem and the purpose of the research. The results showed that the planning of supervisory coaching of Islamic Religious Education teachers was developed based on the results of supervision in the previous year and contained coaching priorities with their achievement targets in the short, medium-term, and long term